PERSEPSI WANITA TERHADAP PELAYANAN KLIMAKTERIUM OLEH BIDAN - Nina Primasari; Fauziah Yulfitria; Erika Yulita Ichwan; Ika Yudianti (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
Background : Menopause is a process in the natural reproductive cycle experienced by every woman. (Suparni & Astutik, 2016). In order for life to take place in satisfaction and happiness, women need to make preparations to deal with it by knowing the organs, their functions, and knowing the events of the climacterium and menopause (Pieter, 2011). Data from the World Health Organization (WHO) in 2014 that stated that by 2030 the number of women worldwide entering menopause is estimated at 1.2 billion people. In 2016 in Indonesia reached 14 million menopausal women or 7.4% of the total population. Continuous midwifery care provides professional health services by midwives provided to women throughout the reproductive cycle. Services are provided in order in the community, Health Center, Midwife Self-Practice, and Hospital. Purpose : Known Perception of Women Towards Klikmaterium Services By Midwives In PMB North Jakarta Region. Method : Quantitative research with cross sectional. The population was all women who visited the midwife's self-sustaining practice with a sample count of 96 people and sampling with random sampling techniques. Data processing uses univariate and multivariate analysis. Results and discussion : The results of the analysis there are two variables have a value of p < 0.05, namely education and information, so that it is concluded that the variables of education and information are significantly related to the perception of climactterium services in women. From multivariate results there are two variables that become confounding variables because in multivariate analysis, experiencing changes in OR > 10%, namely general knowledge and belief. The results of the multivariate analysis, the highest dominant factor found in the education variable (OR = 3,488) related to the perception of klimactterium services, meaning that respondents who have higher education will have a 3,488 times better chance of having a better perception of klimactterium services compared to respondents whose education is low after being controlled by information. Conclusions and advice : It is necessary to open a special counseling service program for pre-menopausal women, so as to provide sufficient knowledge in the face of menopause and can make the best use of the service.